The influence of prospector and defender strategieson dynamic capabilities, innovation, and financial effectiveness in Vietnamese service SMEs - Thu-Hang Le; Mai Ngoc Khuong (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: The article examines the relationships between prospector and defender-oriented SMEs, dynamic capabilities, innovation, and financial effectiveness within the service sector through the resource-based view (RBV) and dynamic capabilities view (DCV) perspectives. Research Design & Methods: We tested a research model using data collected from 421 usable responses of service SME founders and managers in Southeast Vietnam. We employed PLS-SEM through SmartPLS software for analysis. Findings: We found that prospectors significantly enhance dynamic capabilities more than defenders. Prospectors positively influence innovation, whereas defenders do not. However, dynamic capabilities drive innovation within SMEs. While we found no direct link between dynamic capabilities and financial effectiveness, innovation was a key predictor of SME effectiveness. Moreover, dynamic capabilities and innovation mediate the relationship between strategic orientations and SME effectiveness. Implications & Recommendations: This study holds valuable implications for both SME strategists and scholars. It sheds light on the strategic pathways crucial for service SMEs, stressing the significance of aligning strategic directions with dynamic capabilities and innovation to boost SME financial effectiveness. Contribution & Value Added: This research offers a novel perspective on strategic pathways for service SMEs in emerging markets, enriching RBV and DCV frameworks with insights specific to developing economies. It extends the Miles and Snow framework by integrating the adaptive cycle, illustrating how dynamic capabilities and innovation empower both prospectors and defenders to navigate change. Moreover, it addresses a gap in the literature by exploring the application of BSC for measuring financial effectiveness within service sectors, paving the way for its integration in measuring SME success in dynamic environments.
Keywords: O31; L80; 330; prospector; defender; dynamic capabilities; innovation; SME effectiveness